The diversity of understorey birds at Gunung Gading National Park, Sarawak - Nur Azirah, Binti Mohamad Arif (Universiti Malaysia Sarawak, UNIMAS, 2012)
The diversity of understorey birds at Gunung Gading National Park was studied. This study was carried out by using mist nets with total fort of 177 nets days which translated to 2124 net hours. The mist net were checked every two hours interval from 0600 to 1800. A total 114 individuals of understorey birds representing 13 families comprising 38 species were recorded during this study. The most diverse family was Pycnonotidae and Timaliidae with both comprised of 9 species captured and followed by Muscicapidae representing 4 species. Little spiderhunter was the most abundance species with 22 individuals (19.13%) followed by Yellow-bellied bulbul with 10 individuals (8.70%) and Rufous backed kingfisher (6.96%) representing 8 individuals. The species diversity (H’) of understorey birds in Gunung Gading National Park was 3.184. Overall from this study showed that Little spiderhunter was the most diverse species of understorey birds in Gunung Gading National Park.